The influences of organisational culture on email usage in Malaysian private universities - Bali Mahomed, Anuar Shah; Mcgrath, Michael G.; Bong, Zhi Yuh; Othman, Zulbasri; Manavalan, Krishenthy; Raman, Kumaran (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examines the influence of organisational culture on use of email among non-academic workers in Malaysian private universities. For this research regarding the culture in organisations, a scale of measurement was used based upon the concepts that are found in values as well as practices in regards to organisational culture developed by Hofstede et al. (1990) namely Need for Security (NS), Results-Oriented (RO), Job-Oriented (JO) and Closed System (CS). In this study, Technology Acceptance Model (TAM) is used as part of the perspective theory on technology adoption, using the constructs; perceived ease of use (PEOU) and perceived usefulness (PU) as mediator for organisational culture and email usage. Data used in the study was based on questionnaires of 185 non-academic staff from four Malaysian private universities. The study found that all constructs of organisational culture were having significant relationship with perceived ease of use (PEOU) with NS, JO and CS having significant negative relationship while RO has significant positive relationship with PEOU on email usage. For PU constructs, this study found a significant negative relationship between JO and PU while a significant positive relationship of RO with PU on email usage. Finally, only PU had significant positive relationship with email usage while PEOU had significant positive relationship with PU on email usage. This means that the usage of email in Malaysian private universities depend on the user's perception of email usefulness rather than perception of ease of use.